2009
DOI: 10.1111/j.1365-2788.2008.01134.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of language and non‐language skills in pervasive developmental disorders

Abstract: A loss of skill, present in one out of five children with PDD, is associated with a slightly more severe symptomatology as measured by the ADI-R, particularly in the repetitive behaviours domain. Furthermore, although abnormalities are often noticed by the caregivers at the time of regression, the ADI-R reveals that other atypical behaviours were in fact present prior to the onset of regression in most cases. None of the secondary factors investigated were associated with regression. In children unexposed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
59
0
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 36 publications
11
59
0
7
Order By: Relevance
“…Rogers (2004) also reported no differences between regression and non-regression groups on measures of gross motor development, which are identified as reasonable proxies for general CNS dysfunction. Possible associations between autistic regression and immunizations have not been supported within the literature (e.g., Meilleur and Fombonne 2009;Richler et al 2006). Various psychosocial stressors have been examined as possible precipitants of regression, but the roles of such events are not well-established in the literature (see Rogers 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rogers (2004) also reported no differences between regression and non-regression groups on measures of gross motor development, which are identified as reasonable proxies for general CNS dysfunction. Possible associations between autistic regression and immunizations have not been supported within the literature (e.g., Meilleur and Fombonne 2009;Richler et al 2006). Various psychosocial stressors have been examined as possible precipitants of regression, but the roles of such events are not well-established in the literature (see Rogers 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Charman [19] notes that although desirable, reliable early identification is hampered due to regression or loss of skills; by age 2 they may exhibit reduced orienting to name, poorer joint attention, some early motor abnormalities, and reduced emotional expression. Meilleur and Fombonne [20], for example, identified a subgroup of children on the autism spectrum with communication and language loss that occurred between ages 15 and 24 months. The researchers [19,20] note that this regression is rare in other non-ASD early developmental disorders.…”
Section: Issues and Challenges In Diagnosticsmentioning
confidence: 99%
“…Meilleur and Fombonne [20], for example, identified a subgroup of children on the autism spectrum with communication and language loss that occurred between ages 15 and 24 months. The researchers [19,20] note that this regression is rare in other non-ASD early developmental disorders. Recently, however, a longitudinal study of ASD developmental trajectories revealed a toddler-age subgroup of non-ASD siblings with noted declines in cognitive and linguistic skills, underscoring the importance of surveilling the development of these high-risk groups [21].…”
Section: Issues and Challenges In Diagnosticsmentioning
confidence: 99%
“…There is no consensus, however, whether development attained before the loss of skills is typical, or delays and behavioral changes could have been observed but were missed. Thus, some individuals with ASD present developmental regression (DR) defined as definitive or significant loss of previously acquired skills (Baird et al, 2008;Meilleur & Fombonne, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that DR may concomitantly affect different areas of development, resulting in loss of language skills, social interaction and the ability to play (Backes et al, 2013;Baird et al, 2008;Castillo et al, 2008;Jones & Campbell, 2010;Lord, Schulman, & DiLavore, 2004;Luyster et al, 2005;Meilleur & Fombonne, 2009;Tamanaha, Machado, Loebmann, & Perissinoto, 2014;Thurm, Manwaring, Luckenbaugh, Lord, & Swedo, 2014). Explanation for the concomitant occurrence of loss of language, social interaction skills and the ability to play is based on the socio-pragmatic approach in which the acquisition of language is linked to socio-cognitive and socio-interactive bases; that is, the emergence of the linguist symbols (i.e., words) takes place after establishing social and cognitive skills during social interaction (Tomasello, 1999(Tomasello, /2003.…”
Section: Introductionmentioning
confidence: 99%